Influence of Doping Concentration on Dielectric, Optical, and Morphological Properties of PMMA Thin Films - Lyly Nyl Ismail; Habibah Zulkefle; Sukreen Hana Herman; Mohamad Rusop Mahmood (Advances in Materials Science and Engineering)
PMMA thin films were deposited by sol gel spin coating method on ITO substrates. Toluene was used as the solvent to dissolve the PMMA powder. The PMMA concentration was varied from 30 ~ 120 mg. The dielectric properties were measured at frequency of 0 ~ 100 kHz. The dielectric permittivity was in the range of 7.3 to 7.5 which decreased as the PMMA concentration increased. The dielectric loss is in the range of 0.01 ~ –0.01. All samples show dielectric characteristics which have dielectric loss is less than 0.05. The optical properties for thin films were measured at room temperature across 200 ~ 1000 nm wavelength region. All samples are highly transparent. The energy band gaps are in the range of 3.6 eV to 3.9 eV when the PMMA concentration increased. The morphologies of the samples show that all samples are uniform and the surface roughness increased as the concentration increased. From this study, it is known that, the dielectric, optical, and morphology properties were influenced by the amount of PMMA concentration in the solution.